Logit Analysis of Violence Against Women in Marginalized Communities, Eastern Tarai Region of Nepal - Mandal, Umesh K (Tribhuvan University Journal, 2010)
Violence against women is the foremost concern of local- international communities at present. Despite formulating several legal provisions, laws, acts and rules, various forms of violence as physical, sexual and psychological were yet not reduced substantially from parochial value based society. Such violence reduction strategy must be based on proper understanding about responsible factors and their nature, intensity and strength. Thus, it is desirable to identify each individual factor/cause and measure their strengths and make prediction so that they would signify some guidelines for formulation of eradication strategy and welfare development program. With this in mind, present paper examines nineteen individual variables associated with demographic, economic and socio cultural, based on hundred households sampled from study area. Maximum likelihood log it analysis tool was used. Difference at age of marriage, size of cultivated land, occupation of husband and wife, food sufficiency, economic dependency of female, educational status of woman, and marriage frequency of a husband were identified as determining factors contributing to the incidence of violence. Amongst, illiteracy, economic dependency, food deficiency and primary occupation of husband are identified as prime determinants based on measured strength in descending order respectively. The study shows the husbands of illiterate women involve in remarriage and such illiterate women suffer the incidence of violence. The following are ensuring education, providing income-generative employment, making food sufficiency, re-orientation of husband for women’s right, main streaming of single woman, awareness of employment providers, strengthening foreign migration policy recommendations for eliminating the violence against women.